Energy-efficient autonomous solar water-pumping system for permanent-magnet synchronous motors - Antonello, Ricardo; Carraro, M.; Costabeber, Alessando; Tinazzi, Fabio; Zigliotto, M. (Institute of Electrical and Electronics Engineers, 2017)
This paper presents a novel stand–alone solar– powered water pumping system, especially suited for usage in rural or remote areas. The system is primarily designed to reduce both cost and complexity, while simultaneously guaranteeing opti¬mal utilisation of the photovoltaic generator. The use of standard hardware and control architectures ensures ease of installation, service and maintenance. The proposed solution consists of a water pump driven by a permanent magnet synchronous motor (PMSM), controlled by a conventional field oriented control scheme. The photovoltaic array is directly connected to the DC bus of the inverter, with no intermediate power conversion stages. A perturbation based extremum–seeking controller adjusts the motor speed reference to attain the maximum power point opera-tion of the photovoltaic array. Both simulations and experimental results on a full-scale prototype support the effectiveness of the proposed system.